Haiti : Public Expenditure Management and Financial Accountability Review - World Bank (Washington, DC : World Bank, 2012)
Haiti made good progress over the past three years but major challenges remain to accelerating growth and reducing poverty. After the lost decade 1994-2004, marked by political instability and economic decline, Haiti reformed significantly and revived growth, especially in the past three years. Macroeconomic policies implemented since mid-2004 helped restart economic growth, reestablish fiscal discipline, reduce inflation and increase international reserves. Financial sector stability has been maintained though weaknesses have emerged. Significant progress was also achieved in the implementation of economic governance measures, mainly in the area of legal framework, core public institutions and financial management processes and procedures. Notably, basic budget procedures were restored, the public procurement system strengthened, and anti-corruption efforts stepped up. Efforts were also made to improve efficiency and transparency in the management of public enterprises. This wave of reforms led to renewed confidence and translated into higher growth. Real Gross Domestic Product (GDP) is estimated to have grown by 2.3 percent in FY2006, implying an increase of about 0.6 percent in per capita GDP, compared to -0.2 percent in FY2005. The successful implementation of its stabilization program helped Haiti benefit from a three year International Monetary Fund (IMF) - Poverty Reduction and Growth Facility (PRGF) supported program. In addition, in November 2006, Haiti qualified for debt relief under the Enhanced Heavily Indebted Poor Countries (HIPC) Initiative by reaching the decision point under the initiative.